Quality Control of Sputum Smears Examination by Re-Reading in a Tuberculosis Screening - F Majlessi; A Sekhavati; K Qazi Saeedi; A Poorreza (Tehran University of Medical Sciences, 2008)
"nBackground: Sputum smear examination is the basis of diagnosis of tuberculosis and quality control for the correct diagnosis of tuberculosis is necessary. This study was a method survey and performed with 930 smears with the aim to compare the confidence rate of sputum smear examination reported by one laboratory technician with the findings reported by two technicians in a tuberculosis screening program."nMethods: In this method survey study in Qaemshahr, smears collected from one laboratory were sent to another laboratory for re-examination and duplicate reading and the findings were subsequently compared. Cultures were used as a standard control test."nResults: Comparison showed that the rate of agreement between positive and negative findings of both laboratories was %73.8 and %99.3, respectively. First laboratory reading and its culture results were similar in 89% of cases. There was no significant decrease in the frequency of false negative results of smears which were read twice as compared to those which had been read once only."nConclusion: The current method of screening patients suspected with tuberculosis, in which all sputum smears are read by a single technician, is accepted as an accurate and reliable method for the diagnosis of tuberculosis.